2005
DOI: 10.1038/sj.ejcn.1602346
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in food intake, physical activity, and body weight in a predominantly overweight population

Abstract: Objective-To describe seasonal variation in food intake, physical activity, and body weight in a predominantly overweight population. Design-A longitudinal observational study.Setting-Most of the study participants were recruited from a health maintenance organization (HMO) in central Massachusetts, USA. Additional individuals of Hispanic descent were recruited from outside of the HMO population to increase the ethnic diversity of this sample.Subjects-Data from 593 participants, aged 20-70, were used for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
195
8
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 42 publications
22
195
8
10
Order By: Relevance
“…Neither did we observe significant seasonal fluctuations in the proportion of energy derived from protein, which is in agreement with findings from previous reports (29,(32)(33)(34) . Earlier studies have, however, reported seasonal differences in the intake of fat, with the highest intakes occurring during winter (30,31) , spring (12,31) and autumn (32) . We observed that the proportion of energy derived from total fat exhibited seasonal changes was highest in the summer, this being the result of the holiday season and the dietary changes mentioned earlier.…”
Section: Discussionsupporting
confidence: 94%
“…Neither did we observe significant seasonal fluctuations in the proportion of energy derived from protein, which is in agreement with findings from previous reports (29,(32)(33)(34) . Earlier studies have, however, reported seasonal differences in the intake of fat, with the highest intakes occurring during winter (30,31) , spring (12,31) and autumn (32) . We observed that the proportion of energy derived from total fat exhibited seasonal changes was highest in the summer, this being the result of the holiday season and the dietary changes mentioned earlier.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, which was conducted during the period from fall to winter, the observed average body weight increase in the placebo group could be attributed to the generally known seasonal variation in body weight as reported by other researchers. [20][21][22] Similar results were obtained from BMI data (Fig. 1B).…”
Section: Discussionsupporting
confidence: 78%
“…Nutrient scores, such as total energy in kilo-calories and carbohydrate intake, and percentage of energy from fat and carbohydrate were computed from the data collected from the 7DDR. GI, a measurement of carbohydrate quality, was determined from the 7DDR using published tables [21,22]; GL (GI of a food times the amount of carbohydrate eaten divided by 100) was also calculated, as has been previously reported by our group [23,24]. The 7DDR also included a brief validated physical activity assessment described elsewhere [25,26].…”
Section: Baseline Assessment Of Diet and Physical Activitymentioning
confidence: 99%